THE EFFECT OF SERVICE QUALITY TO THE GUEST SATISFACTION : Case Study at Puri Perdana Hotel Blitar) - Intan Permata Sari; Nurul Farida (Universitas Islam Balitar, 2020)
This research is to find out how much the influence of service quality to the guests at Puri Perdana Hotel Blitar. The research object is the receptionist in charge of providing services at the Puri Perdana Blitar Hotel. A sample is a set or part of a population unit. The sample selection is done by using purposive sampling which is the direct appointment of respondents according to the research needs. So the sample size in this study determined 21 respondents who were in Puri Perdana Hotel Blitar. The result of this research is a significant influence of work facilities on the productivity of 54.661.11 Puri Perdana Hotel Blitar employees known ˃, = 0.536 ˃ 0, 433 then Ho is rejected and Ha is accepted. It means that there is an influence between work facilities to the productivity of 54.661.11 Puri Perdana Hotel Blitar employees. The coefficient of determination above is 0.30 or 30%. It means that the variance that occurs in the 30% employee productivity variable is determined by the variance that occurs in the work facilities variable. This understanding is often interpreted the influence of work facilities on employee productivity = 30%, and the remaining 70% are other factors including work motivation, work discipline and others.